2005
DOI: 10.1038/sj.onc.1208696
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of microarray data on pancreatic cancer defines a set of commonly dysregulated genes

Abstract: Pancreatic ductal adenocarcinoma is the eighth most common cancer with the lowest overall 5-year relative survival rate of any tumor type today. Expression profiling using microarrays has been widely used to identify genes associated with pancreatic cancer development. To extract maximum value from the available gene expression data, we applied a meta-analysis to search for commonly differentially expressed genes in pancreatic ductal adenocarcinoma. We obtained data sets from four different gene expression stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
132
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 174 publications
(141 citation statements)
references
References 28 publications
(28 reference statements)
7
132
0
2
Order By: Relevance
“…We and others have recently undertaken such analyses of normal pancreas and pancreatic adenocarcinoma (Crnogorac-Jurcevic et al, 2003;Logsdon et al, 2003;Hustinx et al, 2004;Grutzmann et al, 2005) and our cDNA array data showed overexpression of spermassociated antigen 1 (SPAG1) in cancer cells (Missiaglia et al, 2004).…”
Section: Introductionmentioning
confidence: 83%
“…We and others have recently undertaken such analyses of normal pancreas and pancreatic adenocarcinoma (Crnogorac-Jurcevic et al, 2003;Logsdon et al, 2003;Hustinx et al, 2004;Grutzmann et al, 2005) and our cDNA array data showed overexpression of spermassociated antigen 1 (SPAG1) in cancer cells (Missiaglia et al, 2004).…”
Section: Introductionmentioning
confidence: 83%
“…8), is a transmembrane protein expressed by several bone marrow stromal cell lines and fibroblasts (Ishikawa et al 1995), and overexpressed in myeloma cells and in several solid tumour cell lines showing elevated invasive capacity (Walter-Yohrling et al 2003). Overexpression of BST2 has also been described in pancreatic adenocarcinoma in a recent meta-analysis of expression profile studies (Grutzmann et al 2005). Notably, a humanised anti-HM1.24 antibody has been developed and employed in clinical trials of multiple myeloma patients (Ozaki et al 1999), and immunotherapy against HM1.24 is being developed (Rew et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to previous studies analysing whole tissue samples from pancreatic tumors (IacobuzioDonahue et al, 2003;Grutzmann et al, 2005), we analysed expression of Cav-1 and related signaling molecules in microdissected tissues of normal pancreatic epithelia versus ductal pancreatic adenocarcinoma (Grutzmann et al, 2004). Expression of the genes of interest was measured in eight pancreatic cancer cell lines, seven normal pancreatic epithelia and 11 ductal adenocarcinoma.…”
Section: Cell Cycle Redistribution Does Not Account For Radiosensitivmentioning
confidence: 99%